2021
DOI: 10.1002/btm2.10235
|View full text |Cite
|
Sign up to set email alerts
|

Recreation of a hair follicle regenerative microenvironment: Successes and pitfalls

Abstract: Running head: Successes and pitfalls in HF regenerationThis article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 170 publications
(393 reference statements)
0
26
0
Order By: Relevance
“…To understand the functional differences of DPCs and HMCs in HF development, GO and KEGG enrichment analysis of the DEGs were performed. GO enrichment analysis showed that GO items including cell adhesion, collagen fibril organization, extracellular matrix (ECM) organization, basement membrane, and DNA-binding transcription factor activity were mainly enriched in the upregulated genes of DPCs, which is consistent with the extracellular matrix of DPCs being rich in basement membrane proteins and collagens [ 9 , 58 ]. Moreover, the ECM is also crucial for the communication between hair follicle cells.…”
Section: Discussionmentioning
confidence: 84%
“…To understand the functional differences of DPCs and HMCs in HF development, GO and KEGG enrichment analysis of the DEGs were performed. GO enrichment analysis showed that GO items including cell adhesion, collagen fibril organization, extracellular matrix (ECM) organization, basement membrane, and DNA-binding transcription factor activity were mainly enriched in the upregulated genes of DPCs, which is consistent with the extracellular matrix of DPCs being rich in basement membrane proteins and collagens [ 9 , 58 ]. Moreover, the ECM is also crucial for the communication between hair follicle cells.…”
Section: Discussionmentioning
confidence: 84%
“…Moreover, the different cell types that form the hair follicle intercommunicate to modulate cell proliferation. In this sense, the use of more complex models such as cocultures of keratinocytes, dermal papilla cells or fibroblasts could be of interest to better resemble the hair follicle …”
Section: Resultsmentioning
confidence: 99%
“…Promoting hair growth through cell therapy has been attempted for a long time, but with limited success 12 . Pioneering studies demonstrated that it was possible to promote hair follicle neogenesis with the transplantation of rat vibrissa dermal papillas 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%